Continuance Usage Intention of Mobile Financial Services in Bangladesh during the COVID-19 Pandemic and Beyond: An Empirical Study - Shetu, Sabakun Naher; Md. Muzahidul Islam; Tuhin, Md. Kashedul Wahab; Md Ariful Hoque; Md. Rakibul Hassan, (International Journal of Business and Technopreneurship (IJBT), 2024)
Research on users' behavioural intention and continuation usage intention to adopt Mobile Financial Services (MFSs) is scarce, despite the rapid increase in their usage in developing countries. This study seeks to examine the predicting characteristics and intention of Bangladeshi customers to continue using MFSs for online purchasing during the COVID-19 pandemic and beyond. A theoretical framework was presented and examined. A structured questionnaire survey was used to gather the primary data. The data was gathered using convenience, non-probability sampling technique. A comprehensive analysis was conducted on a sample size of 413 participants using SmartPLS4.0. The study findings indicate that consumers' decisions to continue using MFSs are influenced by ease of use, perceived usefulness, and fear of COVID-19. The research findings indicate that perceived online security, perceived social influences, and perceived lifestyle compatibility do not have a substantial impact. The study investigates the psychological and ecological aspects peculiar to epidemics to elucidate the reasons behind consumers' expectations of continued usage of MFSs for online purchases. Online businesses must exercise caution when deploying MFSs as consumers' usage patterns can undergo unforeseen changes. The theoretical and managerial implications of the study have been incorporated. The study limitations and potential areas for future research were also evaluated.